KEBIJAKAN KRIMINAL DALAM PERTANGGUNGJAWABAN PIDANA BAGI PELAKU ANIMAL ABUSE DI INDONESIA DAN SINGAPURA - Cantik, Okchelita Nettasari Anugrahning; Puspitosari, Hervina (Gapenas Publisher, 2024)
Currently, it is not uncommon for cases to occur which cause the animal to suffer injuries and can even lead to death. Law enforcement against criminal acts of cruelty and abuse of animals. There are many cases of animal crime, such as abuse and abuse of animals by humans. The results of the research show that law enforcement for animal abuse in Indonesia is still considered to be less effective, due to sanctions that are still considered weak, and a lack of public empathy. Due to this, there is still urgency to discuss the comparison of regulations regarding animal abuse in Indonesia with regulations from other countries, namely Singapore. In this research, the Normative Juridical method is used and uses a statutory approach and uses interviews as secondary legal material. This research aims to find out what criminal liability is regarding perpetrators of animal abuse in Indonesia and Singapore as well as what criminal policies are appropriate and efficient for implementing sanctions for perpetrators of animal abuse in Indonesia. The results of this research show that currently the regulations regarding criminal liability for perpetrators of animal abuse in Indonesia are still not appropriate and not in accordance with the provisions of applicable laws and regulations and are still relatively low when compared with the laws and regulations in force in Singapore because of the penalties imposed by Singapore is significantly higher than Indonesia. This is because the Indonesian people still have a low level of understanding regarding animal welfare and there are still certain customs that use animal meat such as dogs as staple food or similar